2018
DOI: 10.2196/jmir.7606
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Users for a Smoking Cessation Mobile App: Quantitative Study

Abstract: BackgroundThe number of mobile apps that support smoking cessation is growing, indicating the potential of the mobile phone as a means to support cessation. Knowledge about the potential end users for cessation apps results in suggestions to target potential user groups in a dissemination strategy, leading to a possible increase in the satisfaction and adherence of cessation apps.ObjectiveThis study aimed to characterize potential end users for a specific mobile health (mHealth) smoking cessation app.MethodsA … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…First, personal innovativeness in IT use is defined as “the willingness of an individual to try out any new information technology” [57]. This concept has been widely used in IT use studies to capture individuals’ intention to adopt technology, both generally [59] and in health care domains [60-62]. In the adaptive use context, Chow et al [63] found that personal innovativeness positively influenced adaptive IT use behavior.…”
Section: Introductionmentioning
confidence: 99%
“…First, personal innovativeness in IT use is defined as “the willingness of an individual to try out any new information technology” [57]. This concept has been widely used in IT use studies to capture individuals’ intention to adopt technology, both generally [59] and in health care domains [60-62]. In the adaptive use context, Chow et al [63] found that personal innovativeness positively influenced adaptive IT use behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These results were dependent on several factors such as age and educational level, with the age of app users being lower (OR=0.97; 95% CI: 0.96-0.98) than that of non-users, and the higher educational level related to higher app usage (OR=1.12; 95% CI: 1.01-1.24) 24 . However, in another study evaluating the characteristics of users of mobile applications to quit smoking, it was found that demographic characteristics such as age and education level were not associated with the attitude towards the use of a tobacco cessation application, but rather depended on characteristics related to the content of the application instead of the general characteristics of the users 25 .…”
Section: Introductionmentioning
confidence: 97%
“…Smoking cessation is beneficial to health at any age and also constitutes an important pillar of COPD treatment [ 8 , 38 ]. In a 2018 study, app characteristics were more relevant for the intention to use a cessation app than demographic characteristics such as age and level of education [ 39 ]. In clinical practice, satisfactory long-term outcomes depend on a personalized approach in the doctor-patient-app triangle, combining face-to-face counseling, pharmacotherapy, and (a) supportive app(s) with medical devices such as a carbon monoxide checker or a spirometer [ 12 ].…”
Section: Discussionmentioning
confidence: 99%